Linking activity and place attachment dimensions in enhancing the sense of place - Ujang, Norsidah; Dola, Kamariah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2007)
Sense of place definition includes the point where the physical form, activity and meaning are intertwined in the people experience of a place. In urban design and place quality research, much has been discussed on the influence of the physical form and activity on the sense of place. However, the linkage between these components with place meaning and attachment has not been adequately explored, in particular on urban streets. This paper highlights the role of activity in supporting attachment to shopping streets in the city centre of Kuala Lumpur. Surveys and face-to-face interviews with users of Jalan Tunku Abdul Rahman (JTAR), Jalan Masjid India (JMI), Jalan Petaling (JP) and Jalan Bukit Bintang (JBB) were conducted to examine their perception of the streets’ activities and its significance to their association with the places. The research demonstrates that activity has strongly influenced place attachment as reflected in the users’ identification of and dependence on the shopping streets. The attachment is the result of constant and long term engagement with the activities, mainly shopping, trading and socio-cultural interaction.